Filtration of Giardia cysts and other substances: Volume 2, Slow sand filtration - Silverman, Gary P., author; Bellamy, William D., author; Hendricks, David W., author; Water Environmental Research Laboratory, Office of Research and Development, U.S. Environmental Protection Agency, Cincinnati, Ohio, publisher (Colorado State University. Libraries, 1984)
Water treatment efficiency of slow sand filtration was studied under various design and operating conditions to ascertain removal of Giardia lamblia cysts, total coliform bacteria, standard plate count bacteria, particles, and turbidity. Filter removals were assessed at hydraulic loading rates of 0.04, 0.12, and 0.40 m/hr, temperatures of 0°, 5°, and 17°C, effective sand sizes of 0.128, 0.278 and 0.615 mm, sand bed depths of 0.48 and 0.97 m, influent Giardia cyst concentrations of 50 to 5000 cysts/liter; and various conditions of filter biological maturity and influent bacteria concentrations. Testing was conducted from July 1981 to December 1983 with nine pilot filters, each 1 foot in diameter. Results showed that slow sand filtration is an effective water treatment technology. Giardia cyst removal was virtually 100 percent for a biologically mature filter. Total and fecal coliform removal was approximately 99 percent. Particle removal averaged 98 percent. Standard plate count bacteria removal ranged from negative removals to 99 percent, depending on the influent concentration. Turbidity displayed a unique ability to pass through the filters, a characteristic not previously reported, and removal ranged from 0 to 40 percent. Changes in process variables resulted in decreased filter efficiency for increased hydraulic loading rate, increased sand size, decreased bed depth, and decreased biological activity. Giardia removal was influenced by the biological maturity of the filter but not by the variables mentioned above. During filter start-up, Giardia removal was 98 percent; and once the filter was mature, removal was virtually complete. Slow sand filtration is effective in removing Giardia cysts and bacteria and should be considered as an alternative to rapid sand filtration during treatment process selection for small communities. As a general principle, on-site pilot testing should precede any selection or installation of a water treatment system. This report covers the period March 1, 1981 to February 28, 1984, and work was completed as of February 28, 1984.
CER83-84WDB-GPS-DWH37b.
This report was submitted in fulfillment of Contract No. CR808650-02 by Colorado State University under the sponsorship of the U.S. Environmental Protection Agency.
Keywords: Water -- Purification -- Slow sand filtration; Drinking water -- Purification -- United States; Filters and filtration; Giardia lamblia